When Goal-Setting Forges Ahead but Stops Short - Asad Islam; Sungoh Kwon; Eema Masood; Nishith Prakash; Shwetlena Sabarwal; Deepak Saraswat (Global Labor Organization (GLO), 2020)
In this study, we use at scale randomized control trial among 18,000 secondary students in 181 schools in Tanzania (Zanzibar) to examine the effects of personal best goal-settings on students' academic performance. We also offer non-financial rewards to students to meet the goals they set. We find that goal-setting has a significant positive impact on student time use, study effort, and self-discipline. However, we do not find any significant impact of goalsetting on test scores. We find that, this could be partially because about 2/3rd of students do not set realistic goals. Third, we find weaker results on time use, study effort, and discipline when we combine goal-setting with non-financial rewards, suggesting that typing goal-setting to extrinsic incentives could weaken its impact. We also find that female students improved on outcomes much more than male students and that students coming from relatively weaker socio-economic backgrounds improved more than their counterparts.
Keywords: D9; I20; I25; O15; O55; 330; Goal-Setting; Recognition Rewards; Student Performance; Zanzibar